The Mental Health in Women with Polycystic Ovary Syndrome (PCOS): A Scoping Review - Dini Asrika Devi; Farida Kartini (Women, Midwives and Midwifery, 2022)
Background: Women of childbearing age with Polycystic Ovary Syndrome (PCOS) are very susceptible to menstrual disorders, stress, and infertility. Psychological comorbidities are also common in women with PCOS, which impair overall quality of life. Although there has been a review of PCOS, it is not related to mental health. Therefore, it is necessary to review articles on mental health for women with PCOS. Purpose: To determine the mental health of women with Polycystic Ovary Syndrome Methods: This literature review applied a scoping review approach adapted to the PRISMA-ScR checklist framework. Three databases were used in the review, namely Pubmed, ESHRE, and SciencDirect. Prisma Flowchart was used for article seletion and the critical appraisal referred to Joanna Briggs Institute (JBI) critical appraisal tool. Results: The database search resulted in 253 relevant topics and generated 10 most relevant articles to the research objectives as the final results. These researches were conducted in various countries using various approaches ranging from qualitative research, cross-sectional study, case control, cohort, and RCT. Three themes were obtained from the data base mapping, namely determinants, effectiveness, and mental health impacts on PCOS women Conclusion: Women with PCOS mostly suffered from psychological disorders, especially at the level of anxiety. There is a correlation between mental health and PCOS, which results in decreased quality of life due to stress/depression, increased anxiety, and poor sleep quality. In this case, Pioglitazone Metformin (PM) is not a sufficient treatment for the symptoms, and thus additional therapy such as cognitive-behavioral therapy (CBT) is needed as assistance.